Chemoprevention with green propolis green propolis extracted in L-lysine versus carcinogenesis promotion with L-lysine in N-Butyl-N-[4-hydroxybutyl] nitrosamine (BBN) induced rat bladder cancer - Dornelas,Conceição Aparecida (2012)
PURPOSE: To determine the effects of green propolis extracted in L-lysine (WSDP) and of L- lysine for 40 weeks on induced rat bladder carcinogenesis. METHODS: The animals (groups I, II, III, IV, V and VI) received BBN during 14 weeks. Group I was treated with propolis 30 days prior received BBN, and then these animals were treated daily with propolis; Groups II and III was treated with subcutaneous and oral propolis (respectively) concurrently with BBN. The animals of Group IV were treated L-lysine; Group V received water subcutaneous; and Group VI received only to BBN. Among the animals not submitted to carcinogenesis induction, Group VII received propolis, Group VIII received L-lysine and Group IX received water. RESULTS: The carcinoma incidence in Group I was lower than that of control (Group VI). The carcinoma multiplicity in Group IV was greater than in Group VI. All animals treated with L-lysine developed carcinomas, and they were also more invasive in Group IV than in controls. On the other hand, Group VIII showed no bladder lesions. CONCLUSION: The WSDP is chemopreventive against rat bladder carcinogenesis, if administered 30 days prior to BBN , and that L-lysine causes promotion of bladder carcinogenesis.